Glyphosate Utilization as the Source of Carbon: Isolation and Identification of new Bacteria - M. Mohsen Nourouzi; T. G. Chuah; Thomas S. Y. Choong; C. J. Lim (E-Journal of Chemistry)
Mixed bacteria from oil palm plantation soil (OPS) were isolated to investigate their ability to utilize glyphosate as carbon source. Results showed that approximately all of the glyphosate was converted to aminomethyl-phosphonic acid (AMPA) (99.5%). It is worthy to note that mixed bacteria were able to degrade only 2% of AMPA to further metabolites. Two bacterial strains i.e. Stenotrophomonas maltophilia and Providencia alcalifaciens were obtained from enrichment culture. Bacterial isolates were cultured individually on glyphosate as a sole carbon source. It was observed that both isolates were able to convert glyphosate to AMPA.